Impairment of bimanual in-phase movement during recovery from frontal lobe tumor surgery: a case report - Takada, Kozue; Yamaguchi, Takuya; Hyuga, Yuko; Mitsuno, Yuto; Horiguchi, Satoshi; Kinoshita, Masako; Satow, Takeshi (Frontiers in Neuroscience, 2023)
The mechanisms underlying bimanual coordination have not yet been fully elucidated. Here, we evaluated the clinical features of bimanual movement impairment in a patient following surgery for a frontal lobe tumor. The patient was an 80-year-old man who had undergone subtotal tumor resection for a tumor in the right superior frontal gyrus. Histological examination of the resected specimen led to the diagnosis of malignant lymphoma of the diffuse large B-cell type, and the patient subsequently received high-dose methotrexate-based chemotherapy. Postoperatively, the patient had difficulty with bimanual movement, and on the 5th postoperative day we found that the impairment could not be attributed to weakness. Temporal changes in the characteristics of manual movements were analyzed. Bimanual diadochokinesis (opening/closing of the hands, pronation/supination of the forearms, and sequential finger movements) was more disturbed than unilateral movements; in-phase movements were more severely impaired than anti-phase movements. Bimanual movement performance was better when cued using an auditory metronome. On the 15th postoperative day, movements improved. The present observations show that in addition to the disturbance of anti-phase bimanual movements, resection of the frontal lobe involving the supplementary motor area (SMA) and premotor cortex (PMC) can cause transient impairment of in-phase bimanual diadochokinesis, which can be more severe than the impairment of anti-phase movements. The effect of auditory cueing on bimanual skills may be useful in the diagnosis of anatomical localization of the superior frontal gyrus and functional localization of the SMA and PMC and in rehabilitation of patients with brain tumors, as in the case of degenerative movement disorders.